Drop-drop Microextraction Enhanced by Two Opposite Surface Acoustic Waves - Fu Xiang-ting; Zha Yan; Zhang An-liang (Institute of Advanced Engineering and Science, 2013)
A droplet-droplet microextraction enhanced by two surface acoustic waves in opposite propagation directions is proposed. A 2×2 interdigital transducer array with 27.5MHz center frequency was fabricated on a 1280 yx-LiNbO3 piezoelectric substrate using micro-electric technology. Two surface acoustic waves in opposite propagation direction were generated when a RF signal was applied to diagonal interdigital transducers. The movement of extractive matter particles within microextraction solution was accelerated due to the radiation of the surface acoustic waves. Then, the mass transfer between two phases was enhanced. An ionic liquid and an organic dye (acid green-25) solution were used for extraction experiments. Results show that the extraction was greatly enhanced by two surface acoustic waves in opposite propagation directional, and almost finished within 160 seconds when the RF signal power was 27.8dBm.The stability of microextraction solution was also improved due to the two opposite surface acoustic waves. DOI: http://dx.doi.org/10.11591/telkomnika.v11i5.2502